Pengembangan Media Video Pembelajaran Berbasis Contextual Teaching Learning Pada Tema Lingkunganku Tercemar Untuk Menumbuhkan Kemampuan Berpikir Kreatif Siswa SMP: Pengembangan Media Video Pembelajaran Berbasis Contextual Teaching Learning Pada Tema Lingkunganku Tercemar Untuk Menumbuhkan Kemampuan Berpikir Kreatif Siswa SMP - Kurniasih, Yani; Leksono, Suroso Mukti; Nestiadi, Adi (UNIB Press, 2025)
This study is based on the constraints found in the field regarding the science learning process in junior high schools. Learning activities oriented towards contextual learning and students' creative thinking skills have not been implemented optimally. Creative thinking skills can be implemented by developing them through video learning media based on Contextual Teaching Learning. This study aims to determine the level of validation of video learning media based on Contextual Teaching Learning on the theme of my polluted environment to develop the creative thinking skills of junior high school students. The method used is Research & Development (with the 4D model), namely the define, design, development and dissemination stages. The development stage shows the results of the validity of video learning media based on contextual teaching learning on the theme of my polluted environment to develop the creative thinking skills of junior high school students that based on validation by material experts, the percentage value is obtained 88,40% In the category